Characterization of Thermal, Ionic Conductivity and Electrochemical Properties of Some p-Tosylate Anions-Based Protic Ionic Compounds - Arfat Anis; Manawwer Alam; Abdullah Alhamidi; Mohammad Asif Alam; Ravindra Kumar Gupta; Mohammad Tariq; Hamid Shaikh; Anesh Manjaly Poulose; Saeed M. Al-Zahrani (Crystals, 2022)
In the present work, six protic ionic liquid (PIL) compounds based on p-toluene sulfonic acid [PTSA] anion along with different cations viz. tetraethylenepentammonium [TEPA], triethylammonium [TEA], pyridinium [Py], N-methylpiperidinium [Pip], 1-methylimidazolium [Im], and N-methylpyrrolidinium [Pyrr] were synthesized using the standard neutralization reaction method. The structural characterization of these compounds was achieved using FTIR, 1H and 13C NMR spectroscopies. Thermal behavior was studied using differential scanning calorimetry to determine the melting point (Tm) and crystallization (Tc) temperatures. Thermogravimetric analysis was carried out to determine the thermal stability and degradation temperatures (Tdec) and to ascertain the hygroscopic or hydrophobic nature of the synthesized compounds. Structural effects on the outcome of various properties were witnessed and discussed in detail. Electrochemical impedance spectroscopy was utilized to study the electrical transport properties of the PILs at different temperatures. Cyclic voltammetry was performed to analyze the electrochemical stability of these PILs. Low values of activation energy indicating easy proton transportation along with good electrochemical stability make the PILs a potential candidate for use in the preparation of polymer electrolytes membranes for fuel cell applications.